2020
DOI: 10.1001/jamaneurol.2019.3983
|View full text |Cite
|
Sign up to set email alerts
|

The Narrowing Path for Nilotinib and Other Potential Disease-Modifying Therapies for Parkinson Disease

Abstract: Nilotinib hydrochloride, an Abelson tyrosine kinase inhibitor used in the treatment of chronic myeloid leukemia, has been in the neurology news since the results of the open-label, phase 1 study in a small group of patients with advanced Parkinson disease (PD) and dementia with Lewy bodies was reported at the Society for Neuroscience in Chicago in October 2015. The extensive media coverage that followed, supported by videos of nilotinib-treated participants getting up and walking from their wheelchairs, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In contrast, the 2020 double-blind, placebo-controlled study reported significantly higher homovanillic acid levels in the CSF in the 150-mg nilotinib group but not in the 300-mg group at 12 months . Similar concerns regarding interpretation of the biomarker data were expressed in the Editorial that accompanied Pagan et al publication.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, the 2020 double-blind, placebo-controlled study reported significantly higher homovanillic acid levels in the CSF in the 150-mg nilotinib group but not in the 300-mg group at 12 months . Similar concerns regarding interpretation of the biomarker data were expressed in the Editorial that accompanied Pagan et al publication.…”
Section: Discussionmentioning
confidence: 92%
“…While the number of cases undergoing immune modulation, chemotherapy, and/or radiation in our sample is anticipated to be low due to the predominant cancer subtype, we cannot discount the possibility that some may have undergone treatment and that such treatment influenced the outcome. Although data from a phase 2 clinical trial of nilotinib in PD showed some concerns regarding safety and questionable preliminary evidence of efficacy, the role of immune modulators as a disease-modifying strategy in PD continues to be a topic under active investigation (28,29). Due to multiple dopaminergic dose changes between clinic visits, we could not evaluate the effect of medications and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nilotinib has been shown to attenuate exogenously expressed SNCA levels in mice and reduce SNCA-induced nigral degeneration ( Wong and Krainc, 2017 ). However, because there was no placebo group in this study and significant baseline differences between the two small groups, it was impossible to comment on any potential clinical benefits of the medicine ( Espay et al, 2020 ). Despite the promising results of preclinical research and the fact that another trial (NILO-PD) is now underway in the United States, there is no convincing evidence of nilotinib’s efficacy in PD patients ( Stoker et al, 2018 ).…”
Section: Available Treatments and Their Limitationsmentioning
confidence: 98%